Effect of Early Initiation of Breastfeeding on Exclusive Breastfeeding and Stunting: A Meta-Analysis - Nisa, Tsamarah Iffah Zahrotin; Adriani, Rita Benya; Murti, Bhisma (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2022)
Background: Exclusive breastfeeding is the act of giving breast milk to babies from 0 to 6 months of age without giving any additional food or drinks, other than medicines. Stunting is a nutritional problem in which there is a linear growth disorder caused by chronic nutritional problems and recurrent infections characterized by a height-for-age index (TB/U) where the Z score is less than -2 SD. Early initiation of breastfeeding is one of the factors that influence exclusive breastfeeding and the incidence of stunting. This study aims to examine the effect of early initiation of breastfeeding on exclusive breastfeeding and the incidence of stunting.Subjects and Method: Meta-analysis was carried out using the PRISMA flowchart and the PICO model (Population: mothers and children 0 to 59 months, Intervention: early initiation of breastfeeding, Comparison: no initiation of early breastfeeding, Outcome: exclusive breastfeeding and stunting). The databases used are PubMed, Science Direct, and Google Schoolar with keywords ((early breastfeeding initiation OR skin to skin contact OR breast crawl) AND (exclusive breastfeeding OR breast feeding) AND (stunting)). There were 19 cross-sectional studies published in 2012-2022 that met the inclusion criteria. Analysis was performed with Revman 5.3.Results: 19 articles with a cross-sectional study design originating from Bangladesh, China, Congo, Ecuador, Ethiopia, India, Indonesia, Malawi, Romania, Rwanda, Spain, and Tanzania involving 160,080 mothers and children 0 to 59 months. A meta-analysis of 11 cross-sectional studies showed that mothers and babies who initiated early breastfeeding were 2.16 times more likely to exclusively breastfeed than those who did not initiate early breastfeeding (aOR= 2.16, 95% CI = 1.76 to 2.65; p<0.001). A meta-analysis of 8 cross-sectional studies showed that mothers and babies who initiated early breastfeeding had a 0.89 times chance of not being stunted compared to those who did not initiate early breastfeeding (aOR= 0.89, 95% CI = 0.84 to 0.94; p<0.001 ).Conclusion: Early initiation of breastfeeding can increase exclusive breastfeeding. Early initiation of breastfeeding can reduce the incidence of stunting. Keywords: Exclusive Breastfeeding, Stunting Incidence, Early Breastfeeding Initiation, Meta-Analysis. Correspondence: Tsamarah Iffah Zahrotin Nisa. Master’s Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: tsamaraiffah@gmail.com. Mobile: +6285736314422.